DOI: 10.11606/t.5.2017.tde-06032017-104537
|View full text |Cite
|
Sign up to set email alerts
|

Vírus da Hepatite C e Células Mononucleares do Sangue Periférico

Abstract: ©reprodução autorizada pelo autor Garcia, Gabriella Teixeira Vírus da hepatite C e células mononucleares do sangue periférico / Gabriella Teixeira Garcia. --São Paulo, 2016. Tese ( A hepatite C é uma doença que leva à inflamação do fígado, sendo causada pelo vírus da hepatite C (VHC). Estima-se que existam 130 a 170 milhões de casos de infecção crônica pelo VHC por todo o mundo. Apesar do VHC ser principalmente hepatotrópico, foi evidenciada a detecção de RNA viral em células mononucleares do sangue periféri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Throughout this study, it was observed that there are component cells of the immune system that act as a line of defense related to the infection of the virus existing in the human organism, but these responses likely to vary according to the stage in which the disease is found on the host [3]. Among the immune system cells that act in response to viral infection, we can mention: interferons type I (IFNα and IFNβ), type II (IFNγ) and type III (IFNλ), Natural Killers cells (NK), Neutralizing antibodies and TCD4 + and TCD8 + cells [4].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Throughout this study, it was observed that there are component cells of the immune system that act as a line of defense related to the infection of the virus existing in the human organism, but these responses likely to vary according to the stage in which the disease is found on the host [3]. Among the immune system cells that act in response to viral infection, we can mention: interferons type I (IFNα and IFNβ), type II (IFNγ) and type III (IFNλ), Natural Killers cells (NK), Neutralizing antibodies and TCD4 + and TCD8 + cells [4].…”
Section: Resultsmentioning
confidence: 99%
“…NK cells during the acute phase release the production of IFNγ, an important viral control factor that allows most precise elimination of viral load, through the inhibition of HCV replication [10]. However, in the chronic phase this cell decreases its capacity of liberate IFNγ and increases the production of cytotoxicity that takes to liver damage [3].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations